Astrocyte-neuron interaction in diphenyl ditelluride toxicity directed to the cytoskeleton. (15th March 2017) - Heimfarth, Luana; da Silva Ferreira, Fernanda; Pierozan, Paula; Mingori, Moara Rodrigues; Moreira, José Cláudio Fonseca; da Rocha, João Batista Teixeira; Pessoa-Pureur, Regina
Graphical abstract: Highlights: Diphenyl ditelluride is toxic to the cytoskeleton of neural cells in vitro . Hypophosphorylation disrupts cytoskeletal homeostasis and causes cell dysfunction. Calcium signaling underlies hypophosphorylation of intermediate filaments. Actin disorganization causes altered astrocyte morphology. Astrocyte cytoskeleton is more susceptible than neuronal cytoskeleton. Abstract: Diphenylditelluride (PhTe)2 is a neurotoxin that disrupts cytoskeletal homeostasis. We are showing that different concentrations of (PhTe)2 caused hypophosphorylation of glial fibrillary acidic protein (GFAP), vimentin and neurofilament subunits (NFL, NFM and NFH) and altered actin organization in co-cultured astrocytes and neurons from cerebral cortex of rats. These mechanisms were mediated by N-methyl-d -aspartate (NMDA) receptors without participation of either L-type voltage-dependent calcium channels (L-VDCC) or metabotropic glutamate receptors. Upregulated Ca 2+ influx downstream of NMDA receptors activated Ca 2+ -dependent protein phosphatase 2B (PP2B) causing hypophosphorylation of astrocyte and neuron IFs. Immunocytochemistry showed that hypophosphorylated intermediate filaments (IF) failed to disrupt their organization into the cytoskeleton. However, phalloidin-actin-FITC stained cytoskeletone videnced misregulation of actin distribution, cell spreading and increased stress fibers in astrocytes. βIII tubulin staining showed that neurite meshworks are not altered by (PhTe)2, suggesting greater susceptibility of astrocytes than neurons to (PheTe)2 toxicity. These findings indicate that signals leading to IF hypophosphorylation fail to disrupt the cytoskeletal IF meshwork of interacting astrocytes and neurons in vitro however astrocyte actin network seems more susceptible. Our findings support that intracellular Ca 2+ is one of the crucial signals that modulate the action of (PhTe)2 in co-cultured astrocytes and neurons and highlights the cytoskeleton as an end-point of the neurotoxicity of this compound. Cytoskeletal misregulation is associated with cell dysfunction, therefore, the understanding of the molecular mechanisms mediating the neurotoxicity of this compound is a matter of increasing interest since tellurium compounds are increasingly released in the environment.